The ageing effect on low density lipoprotein to high density lipoprotein ratio between national rugby players and untrained males - Tung, I. W.; Wei, C. H.; Huang, S. C. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Low density lipoprotein (LDL-C) has been designated as bad cholesterol since plasma levels are associated with increased deposition of cholesterol in arterial walls and a higher incidence of heart attacks. Atherosclerosis and heart disease are associated with the level of LDL-C and HDL-C and the ratio of LDL-C to HDL-C has been extremely useful in estimating heart disease risk. The American Heart Association (AHA) verified that heredity, being a male and ageing are belong to unchanged risk factors. Rugby is one of the strongest sports of all athletic items. It is valuable to detect the aging responses in those stock males. The purpose of the study was to detect and compare the different ageing effects on the LDL-L/HDL-C ratio between national rugby players and untrained males. Methods Forty five national rugby players and 97 untrained males volunteered as subjects for the study. They were divided into four groups representing different age groups: 21-30 yrs, 31-40yrs, 41-50yrs, and over 51 yrs. LDL-C was measured by the PVS method and HDL-C was quantified by the phosphotungstic acid- MgCl2 precipitation method. ANOVA, L.S.D. (least significant difference) and t-tests were used to check the level of significance between different ages and groups. Results The results indicated that the ratio of LDL-C/HDL-C was significantly different (P<0.01) only in the 41-50yrs age category. The ratios for groups over 51yrs of age (2.023 and 2.109) were considerably lower than the criteria b NECP classification (>3.53). From the data analysis, it may be concluded that ageing has no significant effect on the ratio of LDL-C/HDL-C both in rugby players and untrained persons.